2000
DOI: 10.1152/jappl.2000.89.3.1046
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in skeletal perfusion with simulated microgravity: a possible mechanism for bone remodeling

Abstract: Bone loss occurs as a consequence of exposure to microgravity. Using the hindlimb-unloaded rat to model spaceflight, this study had as its purpose to determine whether skeletal unloading and cephalic fluid shifts alter bone blood flow. We hypothesized that perfusion would be diminished in the hindlimb bones and increased in skeletal structures of the forelimbs and head. Using radiolabeled microspheres, we measured skeletal perfusion during control standing and after 10 min, 7 days, and 28 days of hindlimb unlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
167
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(174 citation statements)
references
References 47 publications
6
167
0
1
Order By: Relevance
“…In addition, OPN may have a role in alterations of blood flow in hind limbs of unloaded animals, because OPN is reported to be involved in vasculogenesis (Asou et al 2001, Yumoto et al 2002, Pritzker et al 2004, Cheriyath & Hussein, 2005. Blood perfusion is reduced in the bones of the hind limbs of tail-suspended animals (Colleran et al 2000). The loss of alkaline phosphatase activity after unloading is closely associated with the suppression of platelet endothelial cell adhesion molecule-1 (CD31) signaling on the bone marrow cell surface (Sakuma-Zenke et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, OPN may have a role in alterations of blood flow in hind limbs of unloaded animals, because OPN is reported to be involved in vasculogenesis (Asou et al 2001, Yumoto et al 2002, Pritzker et al 2004, Cheriyath & Hussein, 2005. Blood perfusion is reduced in the bones of the hind limbs of tail-suspended animals (Colleran et al 2000). The loss of alkaline phosphatase activity after unloading is closely associated with the suppression of platelet endothelial cell adhesion molecule-1 (CD31) signaling on the bone marrow cell surface (Sakuma-Zenke et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, even a short period of skeletal unloading has been associated with significant decreases in bone blood flow (109). In a recent study, rats were subjected to 7 or 14 days of hindlimb unloading, then blood flow and vascular resistance were quantified following reloading (35).…”
Section: Blood Flow For Maintenance Of Bonementioning
confidence: 99%
“…For instance, in the rat, an hindlimb unloading experiment which simulates microgravity, the blood perfusion in femur, tibia and bone marrow were significantly decreased. This blood supply change corresponded to the unloading-induced bone loss (Colleran et al, 2000). This suggested that bone vascularization might be implicated in the unloading-induced bone loss.…”
Section: Introductionmentioning
confidence: 70%